Combining Ability And Gene Action For Cooking Quality Traits In Nutrient Rich Rice (Oryza Sativa L.) Crosses (Applied Biological Research, 2019)
The present study was conducted in two consecutive seasons (2014 and 2015) at  Agriculture College, Warrangal (India) to assess the combining ability of hybrid  rice (Oryza sativa) for various cooking quality parameters. The genotypes  involved in the study comprised of 45 F1hybrids generated from 10 parents and  two promising check varieties viz., BPT 5204 and Chittimuthyalu. In present  study, the magnitude of specific combining ability variances was found higher  than general combining ability for all the quality characters studied, except for  kernel length, kernel length/breadth ratio and kernel elongation ratio. This  indicated the greater role of non-additive gene action in controlling most of these  traits. The best specific crosses for cooking quality traits were WGL-32100  x RP-Bio-5478-185 (high x low), Ramappa x RP-Bio-5478-176 (high x low)  and Ramappa x RP-Bio-5478 -185 (high x low) and interestingly these  crosses involved parent Ramappa. These crosses were highly promising for  cooking quality traits.
Keywords: Combining ability; cooking quality; gene action; rice